Dates and demography: are radiometric dates a robust proxy for long‐term prehistoric demographic change?. (April 2015) - Attenbrow, Val; Hiscock, Peter
Abstract: Can archaeologists describe human population size and population growth in prehistoric Australia? This question is at the heart of some of the most intense debates about Australian prehistory: investigations into the spread of people into Australia, the rate of dispersal of people across the continent and the impact of colonisers on the environment. Australian researchers have proposed explicit models of population change based on measurements of quantities of "things" as proxies for regional and continental‐wide demographic change, the most common being numbers of habitation sites and/or numbers of artefacts per millennium. Recent researchers have focused on the number of radiometric dates as the proxy for numbers of people. This paper offers an overview of existing models, concluding with a brief critique of the proposition that number of dates per unit time must be reflecting demographic patterns. We suggest that alternative and novel interpretations of large compiled radiometric databases be considered, as these data can contribute to research questions beyond those of demography. Expanding the range of research agendas that employ radiometric datasets may repay the labour invested in their compilation while allowing exploration of the diverse questions about the Australian past that remain unanswered.